PENYELESAIAN TINDAK PIDANA KECELAKAAN LALU LINTAS BERDASARKAN RESTORATIF JUSTICE DI KEPOLISIAN RESORT KABUPATEN LAMANDAU PROVINSI KALIMANTAN TENGAH - Viktor, Feri Jhon (Gapenas Publisher, 2024)
This study aims to explore and analyze the application of the Restorative Justice approach in solving traffic accident crimes in the Lamandau Regency Resort Police, Central Kalimantan Province. The research method used is qualitative with a case study approach. Data was obtained through in-depth interviews with police officers, victims, and perpetrators of accidents, as well as direct observation of the case resolution process. The results showed that the Restorative Justice approach has been applied in various stages of solving traffic accident cases, ranging from mediation to the establishment of restorative agreements between perpetrators, victims, and affected communities. This research provides insight into the effectiveness of the Restorative Justice approach in the context of law enforcement at the local level as well as the challenges faced in its implementation. The implications of these findings can be the basis for public policy and legal practitioners in improving law enforcement systems that are more oriented towards restoration and reconciliation in solving traffic accident crimes